Regional workshop on inland fisheries and aquaculture in central Asia: status and development prospects : (Food and Agriculture Organization of United Nations, 2008)
The objectives of the Workshop were: first, to increase knowledge and understanding among national policy-makers, fisheries and aquaculture sector experts on the status of fisheries and aquaculture development in the Central Asian region by sharing national-level experiences, problems encountered and opportunities for development of the sector with others from the region.